Pengembangan Aplikasi Mobile Pendataan Kualitas dan Kuantitas Air Sungai Brantas Kota Batu menggunakan Kerangka Kerja Flutter - Muhammad Lamkhil Bashor; Fais Al Huda; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Batu is a city located in the Daerah Aliran Sungai (DAS) Brantas. This is a main problem for the Batu City Environmental Service (DLH) because the water quality index in Batu is classified as mildly polluted. Monitoring of water quality and pollution load must be carried out as one of the efforts to control pollution, this refers to the Decree of the Minister of Environment Numbers 110 and 115 concerning Determination of Pollution Load Capacity and Determination of Water Quality Status. DLH Batu conducts water quality data collection manually and separately each period. Thus, there is a risk of data loss and difficulty of analysis. The researcher offered a solution by utilizing technology to help monitoring the quality and quantity of river water quickly and precisely in the form of mobile applications that used the Flutter framework. In this study, the model used was Software Development Life Cycle (SDLC) Prototyping and there were 3 system tests performed, validation testing using black box and usability using a system usability scale. The main users of this application are DLH employees in Batu and the citizens can also access the application to view reports only. The test results obtained showed that the validation test results were 100% successful, while the usability test obtained a result of 93 and was included in the acceptable predicate.